The Impact of Different Powdered Mineral Materials on Selected Properties of Aerobic Granular Sludge - Joanna Czarnota (Molecules, 2020)
This study aimed to evaluate and compare the physical, chemical and biological properties of aerobic granular sludge from reactors with the addition of different powdered mineral materials. These properties have a significant impact on the efficiency of systems in which the biomass in granular form is used. Four identical granular sequencing batch reactors (GSBRs) were adopted for the research performed on a laboratory scale (R1—control reactor; R2, R3 and R4—with materials, PK, PG and PL respectively). The results indicate that the addition of powdered mineral materials improved the properties of biomass in reactors. The SVI5/SVI30 ratio values were significantly lower in the reactors with added materials (approx. 1.3 ± 0.3). The mean values of the sludge volume index at 30 min were the lowest in the R2 (39.8 ± 8.6 mL/g) and R4 (32.8 ± 10.7 mL/g) reactors. The settling velocity of biomass was the highest in the R2 reactor (15.4 ± 6.1 m/h). In the early days of the study, the highest extracellular polymeric substances (EPS) content was found in the biomass from the reactors to which the materials with higher Ca and Mg content were added (380.18−598.30 mg/g MLVSS). The rate of specific oxygen uptake (SOUR) by biomass indicated an insufficient biomass content in the R1 reactor—to 7.85 mg O2/(g MLVSS∙h)—while in the reactors with materials, the SOUR values were at the higher levels.